TANTANGAN PENEGAKAN HUKUM LINGKUNGAN INDONESIA TERHADAP PENCEMARAN LIMBAH INDUSTRI DALAM IMPLEMENTASI PRINSIP POLLUTER PAYS HUKUMasi Prinsip Polluter Pays Hukum - Silitonga, Saritua; Lubis, Muhammad Dhobit Azhary (Jurnal Perspektif Hukum, 2025)
Environmental law enforcement in Indonesia continues to face significant challenges in addressing criminal offenses related to industrial waste pollution. Although the Polluter Pays Principle has been formally incorporated into Indonesia’s environmental legal framework, its practical implementation remains inconsistent and often ineffective in ensuring environmental justice and deterrence. This study aims to examine the enforcement of environmental law in cases of industrial waste pollution by analyzing the extent to which the Polluter Pays Principle is applied within legal and policy discourses. Employing a qualitative approach, this research integrates normative–empirical legal analysis with critical discourse analysis of environmental regulations, court decisions, and policy documents. Data were collected through systematic legal document review and case-based analysis of industrial pollution incidents with criminal and administrative implications. The findings reveal a substantial gap between regulatory norms and enforcement practices, particularly in the allocation of environmental restoration costs to polluters. Moreover, the legal and policy language used in regulatory instruments and judicial reasoning tends to weaken the operational role of the Polluter Pays Principle as a mechanism of environmental accountability. This study underscores the urgency of strengthening environmental law enforcement through regulatory harmonization, consistent sanctioning mechanisms, and the reconstruction of legal discourse toward ecological justice and sustainable development. The results contribute both theoretically and practically to the advancement of environmental governance and law enforcement reform in Indonesia.